Experimental and theoretical approaches to the protonation of thiourea: A convenient nucleophile in coordination chemistry revisited - Schiessl, Wolfgang; Summa, Nadine; Weber, Christian; Gubo, Sonja; Dücker-Benfer, Carlos; Puchta, Ralph; van Eikema Hommes, Nico; van Eldik, Rudi (Zeitschrift für Anorganische und Allgemeine Chemie, 2005)
The protonation of thiourea was reinvestigated in aqueous and non-aqueous media using potentiometric, UV-vis, NMR, MS spectroscopy, as well as DFT calculations. In aqueous medium, no evidence for protonation could be found in the pH range 0 to 7, in agreement with typical pK(a) values (acid dissociation constants of protonated thiourea) quoted in the literature of around - 1.2. Most of the protonation constants quoted in the literature are incorrect and apparently refer to pK, values. Protonation of thiourea occurs at a much higher pK, value in methanol and in water-dioxane mixtures, which must be related to the stabilization of the protonated species in such media.
Keywords: protonation; thiourea; NMR studies; DFT calculations; solvent effects